(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ekamoolika prayoga is the common and convenient way of prescribing medicine Ayurveda. Sushrutha samhita is one of the treatises famous for surgery and medicine. Eventhough there are abundant formulations mentioned in by Acharya sushrutha for various diseases there are also many Ekamoolika prayogas which have equal importance. There are single drugs mentioned for both maintainace of health and also treating diseases. We can also find medicines used both internally and externally. There are over 300 Ekamoolika prayoga mentioned in Sushrutha samhita which includes prescription for many diseases such as Krimi, Prameha, Graha Pratishedha, Netra roga, Twak vikara, Udara, Vrana etc. and also single drugs are mentioned for Rasayana, Vajeekarana and Swasthahita purpose. Different Anupana are mentioned based on the different Dosha involved in the disease. Encouraging the use of Ekamoolika prayoga is not only easy and convenient but also econonomical. It aims mainly on conservation thus avoiding the exploitation of drugs which are rare.